A combined machine for collecting and chopping rice straw. Issue 8 (August 2022) - Awad, Mahmoud; Fouda, Osama; Fathy, Wael; El Balkemy, Wael; Egela, Mohsen; El-Fakhrany, Walied; Okasha, Mahmoud
Abstract: Due to the recent high prices of livestock feed in the world and the new sustainable management practices of rice straw, livestock farmers are obligated to either use or purchase rice straw and cut it to desired lengths to feed ruminants. Therefore, this study aimed to construct a combined machine for collecting and chopping rice straw for lengths preferred in feeding ruminants. The combined machine comprises three main units: a picking up unit, a chopping unit, and a takeout unit. Field experiments were performed on average rice straw moisture content of 25% (w.b.) to evaluate the performance of the combined machine, under factors of 1.3, 1.6, 1.9, and 2.2 km h −1 forward speeds, elevator velocities of 0.79, 0.94, and 1.10 m s −1, and chopping knives rotational speeds of 1600, 2000 and 2400 rpm. The obtained results indicated that the consumed specific energy was 90.94 kWh ha −1 to achieve the highest field capacity of 0.24 ha h −1, with collecting efficiency of 95.30% at a forward speed of 2.2 km h −1, elevator velocity of 1.10 m s −1 and rotational speed of 2400 rpm for chopping knives. In order to achieve the highest chopping quality of 95%, it is recommended to operate the elevator velocity at 0.79 m s −1, rotate chopping knives at 2400 rpm, and drive the tractor at a forward speed of 1.3 km h −1 . The total operating cost of the combined machine is lower than the traditional methods by about 49.84%. Abstract : Rice straw; Chopper; Collecting efficiency; Chopping quality.